Analisis Perkembangan Sistem Manajemen Pendidikan di Era Society 5.0 - Siti Umi Khoiriah; Lia Karunia Lam Uli Lubis; Diva Kayla Nazwa Anas (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
Analysis of the development of the education management system in the 5.0 era refers to the paradigm shift in education caused by technological developments and digitalization. Era 5.0 demands education that is more adaptive, responsive and innovative to environmental changes and individual needs. The purpose of this research is to analyze the development of the education system in the 5.0 era. The method in this study uses a library research method or approach. Education management systems in the 5.0 era must be able to integrate technology and data to facilitate more personalized, creative and collaborative learning. In addition, the education management system in the 5.0 era must also be able to develop the competencies needed to face future challenges such as critical thinking skills, creativity, collaboration, communication, and digital literacy. This requires the adoption of technologies such as online-based learning, project-based learning, and game-based learning that can encourage active participation and a more engaging learning experience. Artificial intelligence (Artificial Intelligence) can be used to create learning applications that are personalized and according to student needs. The importance of the involvement of parents and other stakeholders is also a focus in education management systems in the 5.0 era, this involvement helps ensure compatibility between curricula and facilitates the integration of education and career development.